Influence of metal cofactors and water on the catalytic mechanism of creatininase-creatinine in aqueous solution from molecular dynamics simulation and quantum study - Vannajan Sanghiran Lee (2018)
The reaction mechanism of creatinine-creatininase binding to form creatine as a final product has been investigated by using a combined ab initio quantum mechanical/molecular mechanical approach and classical molecular dynamics (MD) simulations. In MD simulations, an X-ray crystal structure of the creatininase/creatinine was modified for creatininase/creatinine complexes and the MD simulations were run for free creatininase and creatinine in water. MD results reveal that two X-ray water molecules can be retained in the active site as catalytic water. The binding free energy from Molecular Mechanics Poisson-Boltzmann Surface Area calculation predicted the strong binding of creatinine with Zn2+, Asp45 and Glu183. Two step mechanisms via Mn2+/Zn2+(as in X-ray structure) and Zn2+/Zn2+were proposed for water adding step and ring opening step with two catalytic waters. The pathway using synchronous transit methods with local density approximations with PWC functional for the fragment in the active region were obtained. Preferable pathway Zn2+/Zn2+was observed due to lower activation energy in water adding step. The calculated energy in the second step for both systems were comparable with the barrier of 26.03 and 24.44 kcal/mol for Mn2+/Zn2+and Zn2+/Zn2+, respectively. © 2010 Springer Science+Business Media B.V.